2007
DOI: 10.1007/s00125-007-0768-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised, glycated LDL selectively influences tissue inhibitor of metalloproteinase-3 gene expression and protein production in human retinal capillary pericytes

Abstract: Aims/hypothesis Matrix metalloproteinases (MMPs) and their natural inhibitors, tissue inhibitor of metalloproteinases (TIMPs), regulate important biological processes including the homeostasis of the extracellular matrix, proteolysis of cell surface proteins, proteinase zymogen activation, angiogenesis and inflammation. Studies have shown that their balance is altered in retinal microvascular tissues in diabetes. Since LDLs modified by oxidation/ glycation are implicated in the pathogenesis of diabetic vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…More recently, we demonstrated that HOG-LDL has unique effects on one of the inhibitors of matrix metalloproteinases, TIMP-3. 20 It is noteworthy that although glycated LDL has less drastic effects than HOG-LDL on pericytes, as witnessed by our gene array study, 17 modification by glycation is important not only for its own effects but also because it may predispose LDL to oxidative damage and enhance its tendency to become sequestered after extravasation, again increasing the likelihood of oxidation. The sublethal effects of oxidized LDL in the retina merit further study, but our present study addresses its lethal effects on pericytes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…More recently, we demonstrated that HOG-LDL has unique effects on one of the inhibitors of matrix metalloproteinases, TIMP-3. 20 It is noteworthy that although glycated LDL has less drastic effects than HOG-LDL on pericytes, as witnessed by our gene array study, 17 modification by glycation is important not only for its own effects but also because it may predispose LDL to oxidative damage and enhance its tendency to become sequestered after extravasation, again increasing the likelihood of oxidation. The sublethal effects of oxidized LDL in the retina merit further study, but our present study addresses its lethal effects on pericytes.…”
Section: Discussionmentioning
confidence: 91%
“…[17][18][19][20] Briefly, HRCPs (Cambrex, Walkersville, MD) were cultured at 37°C with 5% CO 2 in medium containing 5% fetal bovine serum, 0.1% human epithelial growth factor (hEGF), 0.04% hydrocortisone, 0.1% vascular epithelial growth factor (VEGF), 0.4% human fibroblast growth factor (hFGF)-B, 0.1% R 3 -insulinlike growth factor (IGF)-1, 0.1% ascorbic acid, and 0.1% GA-1000 (Clonetics, Walkersville, MD). HRCP from passages 4 to 13 were used.…”
Section: Human Retinal Capillary Pericyte Culturementioning
confidence: 99%
See 1 more Smart Citation
“…There is long-standing experimental evidence that elevated and biochemically altered lipids may confer cytotoxicity to retinal capillary cells [42]. Moreover, some clinical studies have suggested a link between triacylglycerol and retinopathy [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Lyons' team has shown that extravasated and modified LDL and immune-complexed oxLDL are present in the retina of diabetic patients. They have also demonstrated that glycated LDL and/or oxLDL exert cytotoxicity to cultured human retinal capillary endothelial cells [192], pericytes [166,[192][193][194][195], retinal pigment epithelium [165], and Muller glial cells [196]. Finally, these glycated LDL could be shown to cause changes in cell signaling, gene expression, cell apoptosis, and autophagy [165,192,193,195,196].…”
Section: Lipid-and Lipoprotein-related Biomarkersmentioning
confidence: 99%